Meeting Scheduling System (MSS) / Ng Mun Ting - Ng , Mun Ting (2001)
Meeting Scheduling System (MSS) is a web-based system developed to support the organization of meetings, that is for each meeting request, a suitable meeting date can be determine based on constraints like meeting location, equipment and the number of invitees that can attend the meeting. Besides that, Meeting Scheduling System (MSS) allow users to check if the invitees are available to attend a meeting, and will inform participants on details about meetings tl1at involve them. It is to avoid the possibility of scheduling a person to attend two or more meetings at one time. Other than that, Meeting Scheduling System (MSS) is to help user to keep track of availability of staff, maintain meeting room and equipment schedules and others right on user computer desktop. With Meeting Scheduling System (MSS), scheduling and tracking meetings rooms, equipment and other facilities is easier than ever. User can create schedule views with any number of rooms side by side. This makes meeting room scheduling fast, efficient and more professional. Meeting Scheduling System (MSS) is communication and collaboration system. This allows user to communicate effectively via e-mail and to collaborate effectively through a central calendar, meeting system and workflow system. This report will stress on MSS feature and design. The decomposition of MSS into modules and sub-modules, and function and features of each module are described in this document. Every phase throughout the entire development of the Meeting Scheduling System are discussed in this report.